Pengaruh Pengetahuan, Tekanan Waktu dan Motivasi terhadap Kinerja Auditor: Studi Kasus KAP KKSP - Jannah, Zahwatul; Ardiami, Kinanthi Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to identify and obtain empirical evidence regarding the effect of knowledge, time pressure, and motivation on auditor performance. The population of this study was all auditors who worked at the KAP KKSP, consisting of 35 respondents. This study uses a non-probability sampling method with the help of SPSS and uses a saturated sample method. Data was obtained by distributing questionnaires to the auditors. The technique of analyzing the data uses multiple linear regression analysis. The results showed that knowledge (X1) and motivation (X3) affected auditor performance (Y) and time pressure (X2) did not affect auditor performance (Y). Keywords: Knowledge, time pressure, motivation, auditor performance